CYTOGENETIC FEATURES OF B-CELL ACUTE LYMPHOBLASTIC LEUKEMIA WITH INTRACHROMOSOMAL AMPLIFICATION OF CHROMOSOME 21 - Jiantuo Liu; Hongrui Li; Li Jiang; Ping Zhang; Shanlin Zheng; Xuekui Qiu; Haiqin Zhang (Hematology, Transfusion and Cell Therapy)
Objective: To investigate the cytogenetic features and prognosis of B-ALL with iAMP21. Methodology: Retrospective analysis of data from 15 children diagnosed with B-ALL and iAMP21 seen in the Department of Hematology, Union Hospital, Tongji Medical College HUST from 2021 to 2024. Screened patients ranged in age from 1 month to 18-years. All were diagnosed with B-ALL using standard morphological and immunophenotypic criteria. Patients in this study were classified as iAMP21 using the criteria of 5 or more RUNX1 signals per cell and by a ratio of RUNX1 to tel 21q signals exceeding 1. Results: In this study, 15 patients demonstrated 5 or more RUNX1 signals per interphase nucleus. Compared to RUNX1, all cases showed fewer subtelomeric signals in interphase cells, ranging from 1 to 5. The accurate interphase distinction of iAMP21 was made by calculating the ratio of RUNX1 to subtelomeric signals; the minimum and maximum values were 1.67 and more than 10, respectively. Metaphase FISH data were recorded if available. Of the cases, 5 of 15 demonstrated 3 or more extra copies of RUNX1 on a single abnormal chromosome 21 with the morphology of mar,r(21)c and add(21)c. Using MLPA, 4 of 15 cases showed gene deletion, including IKZF1, CDKN2A/B, ETV6, BTG1, and RB1. All cases received chemotherapy according to CCCG-ALL-2020. Induction regimens included a combination of vincristine, prednisone, and pegaspargase with daunorubicin. High-Dose Methotrexate (HD-MTX) and 6-Mercaptopurine (6-MP) were incorporated into consolidation regimens. Maintenance regimens were based on a backbone of daily 6-MP and weekly methotrexate with periodic vincristine and prednisone. 14 achieved remissions, and MRD remained negative; 1 did not achieve remission, and MRD was > 0.01%. Conclusion: iAMP21 is a primary cytogenetic abnormality located in the same region of amplification as the RUNX1 gene and a common region of deletion at the telomere. Some patients display other genetic abnormalities in addition to iAMP21. iAMP21 is associated with inferior outcomes, and patients with this abnormality require more intensive therapy.